2023
DOI: 10.1002/cctc.202300407
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Active ZnO Species on Si‐based Supports with Diverse Textural Properties for Efficient Propane Dehydrogenation

Abstract: Propylene is deemed as a kind of key raw materials with significant value in industrial production. Highly dispersed Zn species are served as active sites in catalyzing propane dehydrogenation reaction (PDH). More importantly, the morphology and textural properties of Si-based support exert the great influence on the formation of active Zn species. Herein, active Zn species were dispersed on macroporous commercial SiO 2 , mesoporous siliceous materials (SBA-15, MCF, DMSN, KIT-6), and microporous silicalite-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
(120 reference statements)
2
1
0
Order By: Relevance
“…Furthermore, it has been observed that the physical adsorption peak intensity of V-KIT-6 is lower than that of KIT-6 (Figure S5). The reduction of acidic −OH on the V-KIT-6 surface may be responsible for this difference. , This result is also supported by the Raman results, which show that Si–O–V formation reduces the Si–OH signaling peak intensity (Figure a).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, it has been observed that the physical adsorption peak intensity of V-KIT-6 is lower than that of KIT-6 (Figure S5). The reduction of acidic −OH on the V-KIT-6 surface may be responsible for this difference. , This result is also supported by the Raman results, which show that Si–O–V formation reduces the Si–OH signaling peak intensity (Figure a).…”
Section: Resultssupporting
confidence: 68%
“…The reduction of acidic −OH on the V-KIT-6 surface may be responsible for this difference. 42,58 This result is also supported by the Raman results, which show that Si−O− V formation reduces the Si−OH signaling peak intensity (Figure 3a).…”
Section: ■ Introductionsupporting
confidence: 72%
“…Recently, Zn species have been explored as active components of dehydrogenation catalysts, in addition to their role as promoters [13][14][15][16]. Moreover, ZnO-based materials, such as ZnO loaded on silicalite-1 or doped with NbO, are usually synthesized via impregnation, ion-exchange, and the pulsed laser deposition method, which could exhibit good propane dehydrogenation performance [17][18][19]. In particular, it has been demonstrated that isolated Zn atoms or highly dispersed ZnO nanoclusters present high propene selectivity and catalytic stability in the PDH system [20].…”
Section: Introductionmentioning
confidence: 99%